Orbitozygomatic Fracture Repairs: Are Antibiotics Necessary?. Issue 4 (December 2015) - Huang, Weber; Lynham, Anthony; Wullschleger, Martin
Orbitozygomatic fractures are one of the most common maxillofacial injuries encountered. This study aims to investigate and review the management and complications of orbitozygomatic fractures at the Royal Brisbane and Women's Hospital (RBWH). Specifically the postoperative infection rate will be closely examined to determine whether adjunctive antibiotics are necessary in its surgical management. A retrospective case selection study of all patients with orbitozygomatic fractures treated at the RBWH in 2011 was performed. The cases were collected from the maxillofacial database. Chart review of the admission with consecutive follow-up of up to 6 weeks including clinical and radiological assessment and consecutive data analysis was performed. A total of 160 patients with orbitozygomatic fractures were managed at the RBWH with three complications. Eighty-five (53.1%) cases were treated surgically and 155 (97.5%) cases had follow-up until 6 weeks postoperatively. Twenty-six surgical cases (16.3%) were treated via elevation without fixation. A further 26 surgical cases (16.3%) were treated with one fixation point, 19 cases (11.9%) with two fixation points, 12 cases (7.5%) with three fixation points, and 2 cases (1.3%) treated with four fixation points. The three complications (1.9%) returned for surgical correction without further consequence; two were due to inadequate cosmesis and one was due to exposure of the fixation plate. No early postoperative infections were seen. This study presents an excellent outcome with minimal early complications of orbitozygomatic fractures treated at the RBWH, a trauma center with high caseload. All operatively treated cases received perioperative antibiotic prophylaxis as per the unit's protocol. With a nil infection rate at the RBWH, future studies should focus on whether the use of prophylactic antibiotics is appropriate.